Special effects on the screen : faking the view from Méliès to motion capture - Lefebvre, Martin; Furstenau, Marc, 1963- (Cinema and technology (Amsterdam, Netherlands), 2022)
Since the very first days of cinema, audiences have marveled at the special effects imagery presented on movie screens. While long relegated to the margins of film studies, special effects have recently become the object of a burgeoning field of scholarship. With the emergence of a digital cinema, and the development of computerized visual effects, film theorists and historians have been reconsidering the traditional accounts of cinematic representation, recognising the important role of special effects. Understood as a constituent part of the cinema, special effects are a major technical but also aesthetic component of filmmaking and an important part of the experience for the audience. In this volume, new directions are charted for the exploration of this indispensable aspect of the cinematic experience. Each of the essays in this collection offers new insight into the theoretical and historical study of special effects. The contributors address the many aspects of special effects, from a variety of perspectives, considering them as a conceptual problem, recounting the history of specific special effects techniques, and analysing notable effects films.